Investigating the separate and interactive associations of trauma and depression on neurocognition in urban dwelling adults. (June 2017) - Karstens, Aimee James; Rubin, Leah H.; Shankman, Stewart A.; Ajilore, Olusola; Libon, David J.; Kumar, Anand; Lamar, Melissa
Abstract: Background: Trauma and depression have each been associated with neurocognitive alterations, but their combined effect on neurocognition is unclear. We investigated the separate and interactive associations of trauma and depression on neurocognition in a sample of ethnically diverse urban dwellers, and explored the impact of age on these effects. Methods: 284 adults aged 30–89 were divided into groups based on their current depression and trauma history. Individuals meeting DSM-IV criteria for depression were considered Depressed (D+) and individuals rated through diagnostic interview as having trauma history were considered positive for Trauma (T+). Resulting Ns were 73 D+T+, 56 D+T-, 68 D-T+, and 87 D-T-. A principal component analysis of neuropsychological scores resulted in a 3-factor solution representing verbal learning/memory/recognition (VERBAL-LMR), visual learning/memory/recognition, and speeded attention/cognitive flexibility accounting for 70.21% of the variance. Results: Multivariable linear regressions adjusting for age revealed that Trauma, regardless of Depression, is associated with worse VERBAL-LMR performance. This Trauma association was driven by verbal list and prose passages learning and memory, but not recognition memory. Age-stratified (<60 versus ≥60 years) regressions revealed the Trauma association was only significant for older adults. No main or interactive effects for Depression were observed. Conclusions: Trauma, regardless of Depression, is associated with worse verbal learning and memory, but not recognition performance. These results suggest that trauma exposure may negatively impact neurocognition. Clinicians working with adults in urban settings should query for trauma in addition to depression when considering subjective and objective measures of neurocognitive functioning, particularly in older adults.